Comparison of thermal ablation and surgery for hyperparathyroidism: a meta-analysis - Cui, Huan-yu; Bai, Xiu-mei; Yang, Hong; He, Yun (International journal of hyperthermia, 2025)
Surgery and thermal ablation are both viable treatment modalities for patients diagnosed with hyperparathyroidism (HPT). However, the comparative efficacy of these approaches remains uncertain. The objective of this meta-analysis is to evaluate the effectiveness of surgical complications and therapeutic strategies in managing HPT. The databases PubMed, EMBASE, the Cochrane Library, the Web of Science, CNKI and Wan Fang were systematically searched from inception to December 12, 2023 to identify relevant studies comparing thermal ablation with surgical parathyroid hormone therapy. Data analysis was conducted using Review Manager Version 5.4. A total of 15 studies were incorporated into the meta-analysis, comprising 1,115 participants drawn from 12 cohort studies and three randomized controlled trials. The results indicated no significant difference in parathyroid hormone levels between the two treatment options (mean difference: 29.25, 95% CI: -4.99-63.69, = 0.09), calcium (MD: 0.00, 95%CI: 0.07-0.08, = 0.94), phosphorus (MD: -0.05, 95% CI: -0.13-0.04, = 0.28) and the risk of persistence and/or recurrence (OR: 1.01, 95% CI: 0.63-1.62, = 0.97). The probability of hoarseness (OR: 0.57, 95% CI: 0.35-0.93, = 0.02) and hypocalcemia (OR: -0.12, 95% CI: -0.19- -0.05, < 0.01) was lower after thermal ablation than with surgery. Comparable results were observed in instances of secondary and primary hyperparathyroidism. It can be concluded that surgery and thermal ablation are effective modalities for treating hyperparathyroidism. Thermal ablation has been shown to reduce the likelihood of hoarseness and hypocalcemia. Further validation of these results necessitates conducting comprehensive multicenter randomized controlled trials.